Fiscal Gimmickry in Europe One-Off Measures and Creative Accounting - Koen, Vincent (OECD Publishing, 2005)
Accounting conventions usually leave some room for judgment, which governments may be tempted to take advantage of, especially when fiscal rules bite or threaten to do so. The European experience over the past decade -- documented here in great detail -- illustrates that fiscal gimmicks come in many different guises, but also that some are less mischievous than others. Logit regression analysis confirms that when deficit rules or, to a lesser extent, debt thresholds tend to become more binding, recourse to gimmicks is more likely. It also suggests that more centralised budget systems are less prone to such gimmickry. The policy implications are clear as regards the virtues of transparent and consistent accounting practices, but more ambiguous regarding the merits or otherwise of one-off measures ...
Keywords: Economics